Evaluasi Program Pendidikan Kecakapan Hidup Perkotaan : (Studi Pada Lembaga Khusus Tata Rias Di Tangerang Selatan - Sembiring, Virgo Agustinus; Cholid, Sofyan (UI Scholars Hub, 2016)
This study aimed to evaluate the achievements of the Urban Life Skills Education program by course institutions bridal makeup and analyze the factors that affect achievement Urban Life Skills Education program by institutions bridal makeup courses in South Tangerang city administration. Quantitative research approach is by using chi-square method. Results showed successful achievement by demonstrating the value of 95% for South Tangerang City. While the success of Makeup Bridal based Graduates Competency Standards reached 73.3% Factors that affect the achievement of program Life Skills Education Urban by course institutions bridal makeup in South Tangerang City among others Competency Standards Graduates Makeup Bride Junior and teaching and learning Non-formal Education by Life Skills Education that includes: theory, practice and education of character.